Analisis Perkawinan Beda Agama dalam Perspektif Hukum Islam Dan UU tentang Perkawinan Berdasarkan UU Nomor 1 Tahun 1974 Dan UUNomor 16 Tahun 2019: Studi Kasus Putusan PN JAKARTA SELATAN Nomor.340/Pdt.P/2021/PN JKT.SEL - Ayu Gusnaety; Benjamin Lemta Luntungan (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2025)
The main problem in this study is that there are still many people who have entered into interfaith marriages but have not submitted a marriage determination letter to the District Court. The purpose of this study is to explain the regulation of interfaith marriages according to Law Number 1 of 1974 and Law Number 16 of 2019 and to explain the legal basis and considerations of the Judge in granting or rejecting an application for interfaith marriage. The research method used is a qualitative method by analyzing the determination of court decisions. From decision Number 340 / Pdt.P / 2021 / PN JKT.SEL, an application for interfaith marriage permits was not granted by the South Jakarta District Court. Considering, that based on the posita of the application of the applicants who have entered into a Catholic marriage in this case the Judge is of the opinion that the arguments of the Applicants' application are contradictory and do not support each other with the petitum of the application. The Judge makes decisions objectively so that there is no social inequality between people who have interfaith marriages in Indonesia. Interfaith marriage is forbidden in Islamic law and also other religious laws, therefore, there needs to be a positive response from scholars and other religious figures to further increase the belief regarding the prohibition of interfaith marriage. It is better if marriage is carried out between people of the same religion.